LRR-Containing Oncofetal Trophoblast Glycoprotein 5T4 Shapes Neural Circuits in Olfactory and Visual Systems - Tsuboi, Akio (Frontiers in Molecular Neuroscience, 2020)
In mammals, the sensory experience can regulate the development of various brain structures, including the cortex, hippocampus, retina, and olfactory bulb (OB). Odor experience-evoked neural activity drives the development of dendrites on excitatory projection neurons in the OB, such as mitral and tufted cells, as well as inhibitory interneurons. OB interneurons are generated continuously in the subventricular zone and differentiate into granule cells (GCs) and periglomerular cells (PGCs). However, it remains unknown what role each type of OB interneuron plays in controlling olfactory behaviors. Recent studies showed that among the various types of OB interneurons, a subtype of GCs expressing oncofetal trophoblast glycoprotein 5T4 is required for simple odor detection and discrimination behaviors. Mouse 5T4 (also known as Tpbg) is a type I membrane glycoprotein whose extracellular domain contains seven leucine-rich repeats (LRRs) sandwiched between characteristic LRR-N and LRR-C regions. Recently, it was found that the developmental expression of 5T4 increases dramatically in the retina just before eye-opening. Single-cell transcriptomics further suggests that 5T4 is involved in the development and maintenance of functional synapses in a subset of retinal interneurons, including rod bipolar cells (RBCs) and amacrine cells (ACs). Collectively, 5T4, expressed in interneurons of the OB and retina, plays a key role in sensory processing in the olfactory and visual systems.